Quality of the teaching process from the perspective of music educators - Милић, Тијана (Norma, 2026)
The subject of this paper is the analysis of the extent to which the prescribed quality standards in the area of Teaching and Learning are achieved from the perspective of music educators. The study is based on teacher self assessment and aims to examine the degree to which the indicators of these standards are implemented in music schools. For the purposes of the research a questionnaire with a Likert type scale was designed covering the indicators of standards 2.1 , 2.3 , 2.4 and 2.5. The instrument demonstrated high reliability (α = 0.86). The sample consisted of 65 teachers from 20 music schools. The results show that teachers highly value the prescribed standards. The highest ratings were given to standards 2.5 Every student has the opportunity to be successful; 2.1 The teacher effectively manages the learning process; 2.3 Students acquire knowledge, adopt values and develop skills and competencies; 2.4 Assessment procedures support further learning. Using parametric statistical techniques, statistically significant differences (p < 0.05) were identified regarding the teachers’ gender, type of teaching and competition related experience in pedagogical practice. These differences were particularly evident in the context of pedagogical optimism and the degree of choice available in the teaching process. The findings highlight the importance of teachers professional experience especially in relation to standards that recognize students’ individual characteristics, promote mutual respect, encourage pedagogical optimism and emphasize the value of quality feedback as an effective approach to achieving long term educational goals in which teachers play a central role.